EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI DALAM PRODUKSI JAHE GAJAH - Prabawa, Bagus Ade Tegar; Dewi, Ratna Komala (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 7 No 1 (2019): MEI 2019, 2019)
ABSTRACT The maximum production can be achieved if using optimum inputs. Production efficiency is influenced by the use of production inputs. The purpose of this research was to examin;: (1) the effect of production factors of jahe gajah; (2) inefficiency and efficiency factor of jahe gajah; (3) farmer's income in jahe gajah farming; and (4) constraints faced in Jahe Gajah production. The research method uses quantitative descriptive methods. The number of samples in this is researc were 66 people determined by the Simple Random Sampling technique. Production efficiency was analyzed using the Stochastic Frontier production function with the Frontier 4.1c program and farmer’s income was analyzed using R/C ratio. The results of the research indicate that; (1) land area variables affect production; (2) education, experience, counseling  dummy variables influence production, while jahe gajah farm is stated to be technically efficient with an average value of 0.910, but not yet allocatively efficient with an average value of 0.668 and not economically efficient with average values of 0.599; (3) the jahe gajah farm has profit R/C ratio 1,7; (4) constraints faced by jahe gajah farmers there is no standards price, difficulty in obtaining market access, and rhizome rotten disease.